2004
DOI: 10.1152/ajpheart.00146.2004
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Po2during extreme hemodilution with hemoglobin site specifically PEGylated at Cys-93(β) in hamster window chamber

Abstract: Intaglietta. Microvascular PO 2 during extreme hemodilution with hemoglobin site specifically PEGylated at Cys-93(␤) in hamster window chamber. Am J Physiol Heart Circ Physiol 287: H1609 -H1617, 2004. First published June 10, 2004 10.1152/ajpheart.00146.2004.-The oxygen transport capacity of nonhypertensive polyethylene glycol (PEG)-conjugated hemoglobin solutions were investigated in the hamster chamber window model. Microvascular measurements were made to determine oxygen delivery in conditions of extreme h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…Animal studies have shown that isolated decreases in p50 [24], increases in n [38], or increases in molecular size [39] all correlate with increased tissue perfusion. In vivo experiments have also shown that Hbs with a combination of high p50 and small molecular size cause vasoconstriction and hypertension [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that isolated decreases in p50 [24], increases in n [38], or increases in molecular size [39] all correlate with increased tissue perfusion. In vivo experiments have also shown that Hbs with a combination of high p50 and small molecular size cause vasoconstriction and hypertension [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…After the level 2 exchange, level 3 exchange was performed with animals randomly divided into two experimental groups by sorting a set of random numbers produced in a random ordering scheme (2). Experimental group 1, labeled ␣␣Hb, was hemodiluted with ␣␣Hb to a Hct of 11%.…”
Section: Methodsmentioning
confidence: 99%
“…Group 2, labeled MP4, was similarly hemodiluted with MP4. This procedure was used to compare with previous studies of extreme hemodilution using OCPEs and oxygen noncarrying plasma expanders (2)(3)(4)26). Results were compared with control (no hemodilution) and to a previous study carried out under identical circumstances using PBH solution (13.1 g hemoglobin/dl) in a modified lactated Ringer solution (Oxyglobin, Biopure; Boston, MA) (3,23).…”
Section: Methodsmentioning
confidence: 99%
“…Progressive hemodilution to a final systemic Hct level of 11% was accomplished with three isovolemic exchange steps. This protocol is described in detail in our previous reports (2,6,39). Briefly, the volume of each exchange-transfusion step was calculated as a percentage of the blood volume, estimated as 7% of body weight.…”
Section: Animal Preparation Investigations Were Performed In Male Gomentioning
confidence: 99%
“…Because mixed blood and dilution material was withdrawn during the exchanges, a 110% blood volume exchange was needed to reduce the functional Hct to 11% (2,6,34,39,42). Dilution material was infused and filtered (in-line, 0.22-m filter) into the jugular vein catheter at a rate of 100 l/min.…”
Section: Animal Preparation Investigations Were Performed In Male Gomentioning
confidence: 99%